Dimensional stability of materials subject to random vibration - Edeson, R.L.; Aglietti, G.S.; Tatnall, A.R.L. (Precision engineering, 2013)
► A test rig was developed to measure microyield in materials subject to random vibration. ► Tests were performed on two materials, one metallic and one non-metallic. ► The metallic sample showed significant residual strain in the presence of a small non-symmetry in loading. ► The residual strain was predicted with reasonable accuracy using an FEA model solved in the time domain using nonlinear kinematic hardening. High precision stable structures are potentially vulnerable to dimensional instability induced by exposure to random vibration. There appears to have been little work in the literature to understand or mitigate structural dimensional instability induced by random vibration. To gain more insight into this issue, a novel test was recently developed to assess the plastic strain response in the 10−5 to 10−6 range for structural materials subjected to specific random vibration loads. The test was based on a four-point bending configuration with an applied random base excitation. Two types of material were tested – an Al alloy and a CFRP. This paper presents the test setup and results in detail. The Al alloy samples were found to grow slightly in length during testing, due to a small non-symmetry in the applied load. An FEA model of the test setup was solved in the time domain for a sequence of cyclic loads whose amplitude was based on their probability of exceedance in the random environment. This model, using nonlinear kinematic hardening, was able to predict the residual strain response observed during testing with good accuracy. The main implication of this finding is that ultra stable structures subject to random vibration should be assembled in the most strain-free state possible to avoid loss of dimensional stability due to cyclic hardening.